2012
DOI: 10.1371/journal.pone.0031188
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Lysyl Oxidase Propeptide Protein Inhibits Growth and Promotes Apoptosis of Pre-Existing Murine Breast Cancer Xenografts

Abstract: Lysyl oxidase propeptide (LOX-PP) ectopic overexpression inhibits the growth of cancer xenografts. Here the ability and mode of action of purified recombinant LOX-PP (rLOX-PP) protein to inhibit the growth of pre-existing xenografts was determined. Experimental approaches employed were direct intratumoral injection (i.t.) of rLOX-PP protein into murine breast cancer NF639 xenografts, and application of a slow release formulation of rLOX-PP implanted adjacent to tumors in NCR nu/nu mice (n = 10). Tumors were mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 47 publications
1
41
0
3
Order By: Relevance
“…However, an equal number of studies have shown that LOX expression is capable of increasing proliferation of certain cell types, for example osteoblasts (24) and breast cancer (34) as well as CRC (discussed shortly). Coupled with reports that the LOX propeptide will inhibit cell proliferation in models of prostate (53) and breast cancer (3,51), data suggests that the precise location of LOX, its activity, its processing, and more importantly the context of its expression are all important in determining its function. It has thus become necessary to reconcile the contrasting roles of the LOX propeptide and the mature enzymatically active LOX in terms of cancer progression, and much work is being done to address this.…”
Section: Lox In Cancermentioning
confidence: 89%
“…However, an equal number of studies have shown that LOX expression is capable of increasing proliferation of certain cell types, for example osteoblasts (24) and breast cancer (34) as well as CRC (discussed shortly). Coupled with reports that the LOX propeptide will inhibit cell proliferation in models of prostate (53) and breast cancer (3,51), data suggests that the precise location of LOX, its activity, its processing, and more importantly the context of its expression are all important in determining its function. It has thus become necessary to reconcile the contrasting roles of the LOX propeptide and the mature enzymatically active LOX in terms of cancer progression, and much work is being done to address this.…”
Section: Lox In Cancermentioning
confidence: 89%
“…Interestingly, increased matrix stiffness alone cannot promote tumor invasion and cooperation with oncogenic signaling is required for malignant progression [51]. On the other hand, opposing actions of the secreted propeptide of LOX (Figure 2) have been reported [53] and recently attributed to antiproliferative and proapoptotic effects [54].…”
Section: Extracellular Functions Of Lysyl Oxidases In Physiology and Pamentioning
confidence: 95%
“…Indeed, it was first named the ras recision gene (rrg) because of its ability to counteract RAS-induced transformation. It has since been demonstrated that the propeptide, possessing no enzymatic activity, is responsible for this anti-tumoral property [9,10] , due to its pro-apoptotic effect [11] . It is less clear if other LOX members share those, or other, anti-tumoral properties.…”
Section: Introductionmentioning
confidence: 99%